2014
DOI: 10.1167/iovs.14-14181
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Crowded Letter Recognition in the Peripheral Visual Field

Abstract: These data show that crowding in adults is unaffected by senescence and provide additional evidence for distinct neural mechanisms mediating surround suppression and visual crowding, since the former shows a significant age effect. Finally, our data suggest that the well-documented age-related decline in peripheral reading ability is not due to age-related changes in visual crowding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 62 publications
(79 reference statements)
2
27
0
Order By: Relevance
“…This result is consistent with previous studies on crowding in peripheral vision using resolution acuity 14,15 and surround suppression studies in central vision using contrast matching tasks 2 ; however, ours is the first direct measurement of crowding and suppression in the same older individuals and specifically using stimuli designed to allow such comparison across tasks. Our observed absence of a correlation between crowding and surround suppression is consistent with previous suggestions of distinct mechanisms underpinning these spatial visual phenomena.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with previous studies on crowding in peripheral vision using resolution acuity 14,15 and surround suppression studies in central vision using contrast matching tasks 2 ; however, ours is the first direct measurement of crowding and suppression in the same older individuals and specifically using stimuli designed to allow such comparison across tasks. Our observed absence of a correlation between crowding and surround suppression is consistent with previous suggestions of distinct mechanisms underpinning these spatial visual phenomena.…”
Section: Discussionsupporting
confidence: 92%
“…15 The authors argued that the fact that crowding is unaffected by aging provides support for mechanistic differences between surround suppression and crowding effects in peripheral vision, given that numerous previous studies have shown alterations to surround suppression of contrast in older adults. However, this hypothesis was not tested directly because surround suppression was not measured.…”
mentioning
confidence: 99%
“…Since we used a crowded word identification task, differences in word identification speed between individuals could have been due to differences in crowded visual acuity. However, crowded letter recognition in the peripheral visual field of normal participants does not change significantly with age (Astle, Blighe, Webb, & McGraw, 2014) and, thus, differences in word identification speed are more likely to reflect differences in temporal processing. Temporal processing speed for identifying strings of random letters has been shown to be slower in the peripheral visual field compared to central vision (Cheong et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the fact that temporal frequency thresholds were similar for both dots/ring condition suggests that crowding did not limit performance in the more dense condition. It is possible that dots in the middle ring may have experienced some crowding from the dots on the outer ring in the radial direction, but this would have been constant across all conditions and likely affected both older and younger groups equally, as studies have shown that aging does not affect crowding strength or critical spacing thresholds (Astle, Blighe, Webb, & McGraw, 2014).…”
Section: Performance With Multiple Targets and The Efficiency Of Divimentioning
confidence: 99%